Methodological aspects in forming a specialist-pedagogue by disciplines of a destige direction - M.D. Pryhodiv (Academy of Cognitive and Natural Sciences, 2006)
In this article, a methodological aspects have considered that influence on process of forming of a special pedagogue by a design in context Bolonia's system of training General traits and distinguishing features of home teaching and European teaching have defined.